"Good citizens and gentlemen" : public and private space at the South African College, 1880-1918 - Swartz, Rebecca (Department of Historical Studies, 2015)
This thesis examines the nature of the distinction between public and private space at the South African College (SAC) between 1880 and 1918. By viewing the College within increasingly wide lenses of analysis, examining the micro-level of student experience, to situating the College within its immediate, national and imperial location, the thesis indicates the ways in which institutions should be seen as products of, and permeable to, their historical contexts. Chapter one begins by examining the gendered identity formation of the College students. This is followed by an in-depth examination of the role of the College Council, in particular, in the "public" life of the Cape, and also in the "private" decision making processes within the College.